Clinical Notes on Herbert Screw Fixation for Fracture of Anterior Mandible. Issue 1 (March 2019) - ElMinshawi, Ahmed; Abdelfattah, Salah; Mubarak, Fahmy
This article aims to present the outcomes of treating anterior mandibular fractures using Herbert's screw. A total of 10 patients were treated for fractures of anterior mandible by open reduction and internal fixation using the Herbert screw. The patients were collected starting from June 2016 to November 2017, at the Department of Craniomaxillofacial Surgery, Nasser Institute for Research and Treatment, Cairo, and Faculty of Dentistry, Ain Shams University, Cairo, Egypt. The follow-up plan was done to evaluate the postoperative clinical outcomes for malocclusion, neurosensory status, hardware failure, malunion/ nonunion, pain, and edema. There were no intraoperative or postoperative complications, except for one case where the Herbert screw was insufficient and needed additional 2.0-mm miniplate at the superior border. The postoperative orthopantomograms revealed satisfactory reduction and fixation of the fractures of all cases. The Herbert screw fixation of anterior mandibular fracture is a reliable technique but sensitive and surgeon dependent and needs further clinical investigation.